DYNAMICS OF LEAF BLIGHT DISEASE CAUSED BY ALTERNARIA ALTERNATA IN GERBERA UNDER PROTECTED CULTIVATION (Journal of Plant Disease Sciences, 2025)
Gerbera is an important flower crop cultivated globally under a wide range of climatic conditions. However, disease occurrence remains a major constraint in protected cultivation, primarily due to the warm and humid environment. Among the various diseases reported in gerbera, leaf blight and powdery mildew are the most devastating. During the present investigation under protected conditions, leaf blight caused by Alternaria alternata was identified as a major recurring disease. Weather conditions during the 29th to 35th standard weeks (July and August) were found to play a significant role in the rapid progression of the disease. This period can therefore be considered as the critical window for leaf blight development in gerbera. The correlation matrix revealed a highly significant and positive relationship between leaf blight severity and relative humidity during the study, highlighting the influence of environmental factors on disease incidence under protected cultivation.
Keywords: Alternaria alternata; Gerbera; Epidemiology; Protected cultivation